2017
DOI: 10.1371/journal.pntd.0005698
|View full text |Cite
|
Sign up to set email alerts
|

High risk for chikungunya virus to initiate an enzootic sylvatic cycle in the tropical Americas

Abstract: BackgroundChikungunya virus (CHIKV) has dispersed in the Americas since 2013, and its range of distribution has overlapped large forested areas. Herein, we assess vector competence of two sylvatic Neotropical mosquito species, Haemagogus leucocelaenus and Aedes terrens, to evaluate the risk of CHIKV to initiate a sylvatic cycle in the continent.Methodology/Principal findingsHaemagogus leucocelaenus and Ae. terrens from the state of Rio de Janeiro, Brazil were orally challenged with the two CHIKV lineages circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…Moreover the hunt for CHIKV reservoir hosts has increased in urgency since 2013, when CHIKV was introduced into the Americas. Recently, Loureno-de-Oliviera and Failloux have shown that several neotropical, sylvatic, primatophilic mosquito species are highly competent vectors for CHIKV, opening the door to spill-back of CHIKV from humans to New World primates [45]. However it is possible, based on the data presented here, that other host species will also be required if CHIKV is to establish a sylvatic cycle in the Americas [23,46].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover the hunt for CHIKV reservoir hosts has increased in urgency since 2013, when CHIKV was introduced into the Americas. Recently, Loureno-de-Oliviera and Failloux have shown that several neotropical, sylvatic, primatophilic mosquito species are highly competent vectors for CHIKV, opening the door to spill-back of CHIKV from humans to New World primates [45]. However it is possible, based on the data presented here, that other host species will also be required if CHIKV is to establish a sylvatic cycle in the Americas [23,46].…”
Section: Discussionmentioning
confidence: 92%
“…Such areas increase permeability for the co-occurrence of hosts and bridge vectors, thereby elevating the risk of zoonotic arbovirus exchange 54 . This has the potential to cause outbreaks of novel diseases in urban populations, or, as is the concern for Zika virus in the Americas, lead to spillback and establishment of sylvatic cycles of transmission that could result in an enduring threat to human health 1 , 55 . Understanding the ecology and behavior of potential bridge vectors is, therefore, critical to understanding the risk of spillover and spillback.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti [126,127,144,161–164,164–166], Ae. albopictus [127,144,162,164–167], Aedes terrens [168], and Haemagogus leucocelaenus [168] are all experimentally competent to transmit chikungunya virus. Chikungunya virus transmission in Ae.…”
Section: Resultsmentioning
confidence: 99%